KOMUNITAS BIVALVIA DAN GASTROPODA DI PANTAI CERMIN SUMATERA UTARA - Raissha Amanda Siregar; Yunasfi Djayus; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Mirror beach are located in the eastern coast of Sumatra has a variety of activities that affect the water quality, and can changes community of Bivalvia and Gastropoda. Information and understanding of environmental change is indispensable in ecosystem monitoring effort. This research aims to determine the status of the water quality, community of bivalves and gastropods in Cermin Beach,North Sumatera. This research had been conducted on June to July 2013 in Cermin Beach, Serdang Bedagai District, North Sumatera. There are three stations observed, station 1 : Tourism activities area; 2 : the mangroves area; 3 : estuary area. There are three sampling in 2 months. There are 11 genera from bivalves class and 12 genera from gastropods class. The highest total data in station 1 is 31.140 ind/m3, in station 2 is 15.714 ind/m3 and station 3 is 86.341 ind/m3. From the highest total data in three stations showed diversity criteria, the spread of the number of individuals and community stability classified as moderate. Eveneses index in three stations still moderate, eveneses values is 0,3 and 0,4. Dominance index value showed 0,23, 0,18, and 0,15 for three stations. It means, there is no type that dominate. Dispersion pattern showed clumped and uniform pattern.Keyword : Cermin Beach, Bivalves and Gastropods